Viability, Sublethal Injury, and Release of Cellular Components From Alicyclobacillus acidoterrestris Spores and Cells After the Application of Physical Treatments, Natural Extracts, or Their Components - Bevilacqua, Antonio; Petruzzi, Leonardo; Speranza, Barbara; Campaniello, Daniela; Ciuffreda, Emanuela; Altieri, Clelia; Sinigaglia, Milena; Corbo, Maria Rosaria (Frontiers in Nutrition, 2021)
Alicyclobacillus acidoterrestris is a spoiling microorganism regarded as one of the most important cause of spoilage of fruit juices and acidic products. In this paper, four strains of A. acidoterrestris (type strain-DSM 3922; two wild strains isolated from soil-C8 and C24; wild strain isolated from a spoiled pear juice- CB1) were treated through natural extracts/active compounds from essential oils, and physical treatments to assess their susceptibility and the presence of sub-lethal injury. The characterization of damage was also performed. The results suggest that it is possible to control A. acidoterrestris through alternative approaches, although the effect relied upon the age of spores. In addition to the mere antimicrobial effect, some treatments could cause a sub-lethal injury on spores. Lemon extract was the most effective treatment for both the antimicrobial effect and the sub-lethal injury, as evidenced by the release of proteins, and calcium dipicolinate (DPA) by fresh spores, and only DPA (with an exception for C8) by old spores. A sub-lethal injury with protein release was also found for physical treatments (US or heating). For the first time, this paper reports on the existence of a sub-lethal injury for A. acidoterrestris and this evidence could be also a challenge, because injured microorganisms could restore their metabolism, or an opportunity to design new preserving treatments.